Modelling the mean stress effect on fatigue life of fibre reinforced plastics. (January 2016) - Flore, D.; Wegener, K.
Highlights: Definition of a new master damage parameter that enables a fatigue life prediction independent from the mean stress. Phenomenological model that can accurately predict the mean stress effect in fibre dominated unidirectional and multidirectional laminates. The model needs only one Woehler curve at R  = 0.1 and static ultimate strengths as input parameters what leads to a huge reduction of the experimental characterization efforts. The model needs one parameter set that captures the characteristics of fibre dominated FRP laminates and can be used for six materials. Abstract: The mean stress influence on fatigue life of carbon and glass fibre reinforced plastics is investigated in detail. A new phenomenological approach is presented to model the mean stress effect in various material systems and fibre dominated stacking sequences. The model is calibrated to fatigue data via a developed fitting-routine that is based on least squares method. The calibration input data is one Woehler curve at R  = 0.1 and the ultimate static strengths in tension and compression loading. The characterization effort is reduced by this significantly. Finally the method is verified successfully by fatigue data of several material systems.